If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + 4y + -2 = 15y + -9 + -5y Reorder the terms: 29 + -2 + 4y = 15y + -9 + -5y Combine like terms: 29 + -2 = 27 27 + 4y = 15y + -9 + -5y Reorder the terms: 27 + 4y = -9 + 15y + -5y Combine like terms: 15y + -5y = 10y 27 + 4y = -9 + 10y Solving 27 + 4y = -9 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. 27 + 4y + -10y = -9 + 10y + -10y Combine like terms: 4y + -10y = -6y 27 + -6y = -9 + 10y + -10y Combine like terms: 10y + -10y = 0 27 + -6y = -9 + 0 27 + -6y = -9 Add '-27' to each side of the equation. 27 + -27 + -6y = -9 + -27 Combine like terms: 27 + -27 = 0 0 + -6y = -9 + -27 -6y = -9 + -27 Combine like terms: -9 + -27 = -36 -6y = -36 Divide each side by '-6'. y = 6 Simplifying y = 6
| 13-2(x+51)=-19 | | 0.35(x+3)-.095(2x+28)= | | 222+194+5=627 | | (3x^2)-(5x)+1=0 | | 12x-7=0 | | 2X=4X/5/3 | | (x+8)-2(6x-4)= | | 2x-9y=14fory | | (5-12i)^1/2 | | 6x^2+4y^2-7x+y+2=0 | | -(x-6)-8(4+x)= | | 8x-4y-6y+5x+10= | | -4x+.66=2.3 | | x-5/2-6=x-4/3 | | m/15=9/32 | | -5x^2-14+x^4=0 | | 4x-5(5-x)= | | (-4y+4)-(-3y-8)=2 | | (8+2)(7+(2+4))=X | | V=LWHfrow | | 7-3(5-10)=67 | | (8+2)(7+(2+2))=X | | (5/11)(6) | | 24x+9=18x+3 | | 3x/3=a-1/3 | | t=(.20+2.15)873.36 | | 2x/3-7=5 | | 8x^2+18x-15=20 | | t=(.15+2.15)873.36 | | -4-22v+8=6-6-9v+6v | | 3(5-3v)+9v=28 | | (5x-2)(6x+3)= |